AB1080 TOCILIZUMAB FOR REFRACTORY DYSTHYROïD MYOPATHY (RDM) : A MONOCENTER OBSERVATIONAL STUDY OF 8 PATIENTS. (June 2019) - Bielefeld, Philip; Baudin, Florian; Blanc, Julie; Bron, Alain; Mouries-Martin, Suzanne; Bouvet, Romain; Devilliers, Hervé
Abstract : Background: Dysthyroïd myopathy (DM) refers to Graves' ophthalmopathy (GO) in 90% of the cases but can also be observed with hypothyroidism, and is responsible for orbital fat and muscles inflammation. In those patients with euthyroidism and no thyroid receptor antibody, a strong argument for DM can be the aspect of the extra ocular muscles. In myositis of other causes, muscle insertions are increased in size. In DM, the insertions are respected and not increased in volume in magnetic resonance imaging. This was the case of our eight patients. Objectives: To describe the efficacy of Tocilizumab (TCZ) in RDM in 8 patients Methods: We conducted a monocenter study of 8 patients with RDM refractory to conventional treatment scheme All patients have been treated following the EUGOGO (European Group on Graves' Orbitopathy) scheme, which consists in weekly infusions of 500 mg prednisolone (4 to 6) followed by weekly infusions of 250 g (4 to 6). One patient had received before oral prednisolone, which is known to be less effective and no other immunosuppressive therapy. The aim was to reduce the clinical activity score (CAS) of the disease to a score of 1 (score composed of 7 items) Results: We studied 8 female patients (16 eyes); mean age at diagnosis 64, 37±9, 37 years. All patients had normal thyroid function at diagnosis.Three patients had a previous history of hashimoto's thyroiditis and the other 5 had no immunological abnormalities. The duration of orbitopathy between first supposed manifestations and therapy onset was 5, 7 months +/- 2, 3. TCZ was introduced at the end of the steroid pulses, or before, during steroid therapy, in 2 patients who did not improve at all their ocular status after 3 steroid infusions. TCZ was used intravenously as a monotherapy, at the classical dosage of 8 mg/kg per infusion, with no other immunosuppressives. According to the classification of severity of the EUGOGO group using the CAS 1, before TCZ, 1 had severe (n=2 eyes) or moderate (n= 14 eyes) disease. Moreover, patients presented exophthalmos (n=16 eyes), strabismus (n=16 eyes), muscle inflammation and volume increase at MRI and severe optic neuropathy (n=1). After a mean of 4 pulses (extremes 1 to 7), all patients experienced improvement with TCZ withdrawal in all due to complete remission in 3 and regression in ocular inflammation in 5. Unfortunately, one patient relapsed two months after the 6th TCZ infusion, despite of initial complete remission and was treated with 4 weekly infusions of rituximab at 375 mg/m 2 with a very good response three months later. Only one patient experienced a severe anal abcess after the first TCZ infusion leading to treatment interruption, but with a good improvement of DM. Improvement of ocular parameters with TCZ therapy. Data are expressed as mean±SD or median [IQR]. (VA : visual acuity; IOP : intra ocular pressure; CAS : clinical activity score) Before tocilizumab after tocilizumab VA 0, 7 (0, 3-1) 0, 9 (0, 7-1) IOP 26, 5 +/-7, 7 21, 1+/-13 CAS 4, 25 +/- 1, 28 1 Conclusion: TCZ seems to be effective in RDM, as previously reported. In case of ineffectiveness or relapse, rituximab may be effective as well. This questions us about a new treatment scheme, which patients could benefit from biotherapies alone for a better and quicker efficiency? References: [1] - Dolman PJ. Grading Severity and Activity in Thyroid Eye Disease. Ophthalmic Plast Reconstr Surg. 2018;34(4S Suppl 1):S34-S40 Disclosure of Interests: Philip Bielefeld Consultant for: ABBVIE, Speakers bureau: ABBVIE, Florian Baudin: None declared, Julie Blanc: None declared, Alain Bron: None declared, Suzanne Mouries-Martin: None declared, Romain Bouvet: None declared, Hervé Devilliers: None declared